Immobilization of heavy metals by fly ash-based geopolymer - Somna, Kiatsuda; Jaturapitakkul, Chai; Kajitvichyanukul, Puangrat; Chindaprasirt, Prinya (Asia-Pacific Journal of Science and Technology, 2017)
This work was focused on immobilization of several types of heavy metal included Ni, Cd and Zn by geopolymer. Effect of each heavy metal on compressive strength was also reported in this work. Initial concentrations of each heavy metal in geopolymer were varied as 1, 7 and 10% by weight. It was found that compressive strengths of heavy metal-contaminated geopolymer were decreased when the initial concent rations of heavy metal increased. Among investigated heavy metal, Ni provided the least adverse affect on compressive strength (168.6 ksc. with 10% by weight of Ni initial concentration) while Zn exerted the most negative affect on compressive strength (80 ksc. with 10% by weight of Zn initial concentration). From TCLP test, the leaching value of nickel from geopolymer was lowest as the leaching value was less than 10 mg/l. In contrast, the leaching value of Cd and Zn were approximately 400 mg/l. In overall consideration, the synthesized geopolymer can be used in immobili-zation of heavy metal.